Internationalization of local enterprises : success factors and challenges. - Low, Amy Yanjun. (2008)
This paper seeks to investigate the key success factors involved in the internationalization process and the challenges faced. The objective is to identify critical success factors that contribute to the success of local enterprises’ internationalizing process and also challenges that hinder the process.